FEATURES OF ENDOCRINE PROFILE IN HYPERTROPHIC AND KELOID SCARS OF SKIN - Maxim Vladimirovich Kobets (Байкальский медицинский журнал)
Background. Given the role of hormones in the regulation of scar formation and remodeling processes, it is advisable to study the features of the hormonal profile in conditions of pathological scars. This will improve the efficiency of diagnosing of scar type and form a pathogenetic basis for the treatment of hypertrophic and keloid scars.Aim. To identify the features of the hormonal profile in conditions of hypertrophic and keloid scars.Materials and methods. The clinical state of the scars and the hormonal profile (10 hormones) were studied in 90 women with hypertrophic, keloid and normotrophic scars (control). Blood was taken before treatment on the 5th–7th day of the menstrual cycle. The results were processed by non-parametric statistics (Me (Q25-Q75), U-test at p<0.05). Correlations between hormones were determined by the method of multiple regression at the coefficient of determination R2>0.7.Results. All patients with pathological scars showed a decrease in cortisol levels. Hypertrophic scars are characterized by an increase in the concentration of follicle-stimulating hormone, a decrease in the concentration of estradiol and testosterone. In patients with keloids, the concentration of growth hormone is increased, the levels of prolactin, luteinizing hormone are reduced. Regression analysis showed that the interdependence of hormones is maximally expressed in conditions of normotrophic scars, while hormones had 1-2 correlations in conditions of pathological scars. At the same time, the qualitative composition and direction of interrelations have changed.Conclusion. Pathological scarring is characterized by a decrease in the level of cortisol in the blood, which is expressed in patients with keloid scars in combination with reduced prolactin. A weakening of hormonal interactions and an imbalance in the system of sex hormones were revealed in conditions of hypertrophic scars. and the increased production of growth hormone in combination with a stable interaction between steroidogenesis and a weakened adaptive ability took place in conditions of keloid scars.